2021
DOI: 10.1186/s13071-021-04642-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of schistosomiasis and its association with anemia among pregnant women: a systematic review and meta-analysis

Abstract: Background Schistosomiasis is a highly prevalent parasitic disease that can lead to adverse maternal and perinatal outcomes. To our knowledge, there has been no systematic review and meta-analysis of schistosomiasis during pregnancy. Methods We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Relevant published studies were searched in international databases (PubMed, Science Direct, Scopus, Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 56 publications
(53 reference statements)
0
19
1
Order By: Relevance
“…Udonsi [9] in Igwun river basin north Bende (37.0%), schistosomiasis is the second leading cause of infectious diseases next to malaria in Africa [10] . According to [11] the pooled prevalence of schistosomiasis during pregnancy was 13.2%. Observations of 12 showed that odds of schistosome infections were lowest among people between (15-24 years of age), caregivers (0.1, 95%), and those who used tap water (0.3, 95%) for domestic purposes.…”
Section: Discussion Of Findingmentioning
confidence: 99%
“…Udonsi [9] in Igwun river basin north Bende (37.0%), schistosomiasis is the second leading cause of infectious diseases next to malaria in Africa [10] . According to [11] the pooled prevalence of schistosomiasis during pregnancy was 13.2%. Observations of 12 showed that odds of schistosome infections were lowest among people between (15-24 years of age), caregivers (0.1, 95%), and those who used tap water (0.3, 95%) for domestic purposes.…”
Section: Discussion Of Findingmentioning
confidence: 99%
“…Regarding schistosomiasis as the second most common parasitic infection in the world and one of the most imperative causes of anemia (Mnkugwe et al 2020), it was logic to interpret the existence of schistosomiasis in ADHD group. Urinary and gastrointestinal schistosomiasis can predispose to iron de ciency anemia either by direct blood loss in urine and stool or by associated schistosomal hypersplenism (Adam et al 2021). On the other hand, Schistosoma infection was reported to be highly associated with learning and memory de cits due to cognitive dysfunction by different mechanisms either directly through eggs deposition in the brain, or indirectly, via infection associated iron-de ciency and malnutrition (Ezeamama et al 2018).…”
Section: )mentioning
confidence: 99%
“…This finding is similar to the review finding that S. mansoni had 8.7% prevalence. 37 Some factors like hand hygiene, eating uncooked food, water source type, bared foot, health education, and deworming were significantly associated with the risk of IPI in the multivariable logistic regression.…”
mentioning
confidence: 92%